Effect of surface functionalisation on the interaction of iron oxide nanoparticles with polymerase chain reaction - Aysan, Ayse Beyza; Knejzlík, Zdeněk; Ulbrich, Pavel; Šoltys, Marek; Zadražil, Aleš; Štěpánek, František (Colloids and surfaces. B, Biointerfaces, 2017)
The combination of nanoparticles with the polymerase chain reaction (PCR) can have benefits such as easier sample handling or higher sensitivity, but also drawbacks such as loss of colloidal stability or inhibition of the PCR. The present work systematically investigates the interaction of magnetic iron oxide nanoparticles (MIONs) with the PCR in terms of colloidal stability and potential PCR inhibition due to interaction between the PCR components and the nanoparticle surface. Several types of MIONs with and without surface functionalisation by sodium citrate, dextran and 3-aminopropyl-triethoxysilane (APTES) were prepared and characterised by Transmission Electron Microscopy (TEM), dynamic light scattering (DLS) and Fourier Transform Infrared (FT-IR) spectroscopy. Colloidal stability in the presence of the PCR components was investigated both at room temperature and under PCR thermo-cycling. Dextran-stabilized MIONs show the best colloidal stability in the PCR mix at both room and elevated temperatures. Citrate- and APTES-stabilised as well as uncoated MIONs show a comparable PCR inhibition near the concentration 0.1mgml-1 while the inhibition of dextran stabilized MIONs became apparent near 0.5mgml-1. It was demonstrated that the PCR could be effectively carried out even in the presence of elevated concentration of MIONs up to 2mgml-1 by choosing the right coating approach and supplementing the reaction mix by critical components, Taq DNA polymerase and Mg2+ ions.
Keywords: Taq DNA polymerase; propylaminy; citronan sodný; velikost částic; silany; polymerázová řetězová reakce; teplota; Polymerase Chain Reaction; Particle Size; Nanoparticles; Adsorption; povrchové vlastnosti; železité sloučeniny; Propylamines; nanoPCR; Particle size; Dextrans; dextrany; nanočástice; koloidy; citráty; Temperature; Sodium Citrate; Silanes; Zeta potential; Citrates; Magnetic nanoparticles; Surface Properties; Ferric Compounds; Colloids